2013
DOI: 10.1155/2013/148317
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Multiepitope Protein for Hepatitis B Diagnosis

Abstract: Hepatitis B is a liver inflammation caused by hepatitis B virus (HBV) and can be diagnosed in clinical stage by hepatitis B core antibody from IgM class (anti-HBcIgM). Hepatitis B core antibody from IgG class (Anti-HBcIgG) appears quickly after IgM, reaching high titers in chronic hepatitis, and remains even after cure. Since hepatitis B core antibody (anti-HBc) is the first antibody identified and sometimes the only marker detected during the course of infection, it can be used both to indicate HBV acute infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…The urgent need for a diagnostic test which offers increased degrees of sensibility and specificity prompted us to develop a recombinant multiepitope protein bearing HCV-specific immunodominant epitopes. Several studies have reported the successful use of multiepitope protein for diagnosis of infectious diseases such as leishmaniasis [ 22 ], hepatitis B [ 23 ], hepatitis C [ 12 ], toxoplasmosis [ 24 ], tuberculosis [ 25 ], leprosy [ 26 ], leptospirosis [ 27 ], dengue [ 28 ], and Chagas disease [ 29 ]. A multiepitope protein (r-HCV-F-MEP) for hepatitis C diagnosis has been previously developed bearing 5 immunodominant regions comprising genotypes circulating worldwide and one Indian isolate [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The urgent need for a diagnostic test which offers increased degrees of sensibility and specificity prompted us to develop a recombinant multiepitope protein bearing HCV-specific immunodominant epitopes. Several studies have reported the successful use of multiepitope protein for diagnosis of infectious diseases such as leishmaniasis [ 22 ], hepatitis B [ 23 ], hepatitis C [ 12 ], toxoplasmosis [ 24 ], tuberculosis [ 25 ], leprosy [ 26 ], leptospirosis [ 27 ], dengue [ 28 ], and Chagas disease [ 29 ]. A multiepitope protein (r-HCV-F-MEP) for hepatitis C diagnosis has been previously developed bearing 5 immunodominant regions comprising genotypes circulating worldwide and one Indian isolate [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of recombinant multiepitop protein over expressed in Escheria coli can be used in diagnostic kit for hepatitis B, with several advantages: lower cost, facilitated manipulations, and elimination of problems concerning concentration of different peptides in the kits, but still it is not determined. 27 To encourage voluntary blood donation should be the first step of prevention. To reduce the risk of transfusionassociated hepatitis B, test for antiHBc IgM may be included in routine screening of donors' blood as it has been proved to be an excellent indicator of occult HBV during window period.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, the use of a diagnostic marker that contains a high density of antibody binding site increases the chances of antibody detection in serum samples and provides the potential to acquire inexpensive diagnostic methods with a high degree of specificity and sensitivity. Therefore, a great possibility to improve diagnostic tests performance exists if multiepitope peptide is applied [48]. Application of multiepitopes antigen in diagnostic tests has been conducted successfully in several studies, employing multiepitope peptide in hepatitis C [49], influenza virus [50], leishmaniasis [51] [52], Trypanosoma cruzi [53], leptospirosis, and Mycobacterium tuberculosis [54,55] as well as T. gondii infection [30].…”
Section: Epitope-based Antigenmentioning
confidence: 99%
“…Alternatively, the use of multiepitope peptide that expresses a high density of conserved antigenic determinant can contribute in achieving a high degree of sensitivity and specificity [48,53]. Multiepitope peptide has been evaluated to obtain specific and standard antigens for serodiagnosis of T. gondii infection.…”
Section: Epitope-based Antigenmentioning
confidence: 99%
See 1 more Smart Citation